2016
DOI: 10.17323/j.jcfr.2073-0438.10.3.2016.5-23
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Independent Directors, Insider Ownership and Scientific Connections on Risky R&D Investments: Evidence from Emerging Markets

Abstract: Anastasia N. Stepanova -  National Research University The Higher School of Economics, E-mail: anstepanova@hse.ru Anna Alexandrovna Tereshchenko - National Research Institute "Higher School of Economics R&D projects in the pharmaceutical industry are extremely risky and bring benefits in the long-run period. Self-interested managers try to avoid risk and underinvest in R&D. In this paper we study the effect of independent directors, insider ownership and scientific connections on R&a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Telaia et al [42] showed that there is a direct relationship between the ability of CEO to raise funds and his/her education, which gets stronger in cases where the CEO has anMBA degree. Stepanova et al [43] confirmed that a higher share of independent directors has a positive correlation with higher R&D investments, as the presence of such directors mitigates the agency problem.…”
Section: Management Of Russian Startupsmentioning
confidence: 96%
“…Telaia et al [42] showed that there is a direct relationship between the ability of CEO to raise funds and his/her education, which gets stronger in cases where the CEO has anMBA degree. Stepanova et al [43] confirmed that a higher share of independent directors has a positive correlation with higher R&D investments, as the presence of such directors mitigates the agency problem.…”
Section: Management Of Russian Startupsmentioning
confidence: 96%
“…Gender diversity also may be a measure of efficiency as it has been shown that female directors may decrease the level of CEO overconfidence [19]. However, there is also evidence that in some markets an increase in the number of independent directors may lead to an increase in R&D investments [20], which are associated with high risk and overconfidence.…”
Section: Higher School Of Economicsmentioning
confidence: 99%